Quantifying the Influence of Wedge Pressure, Age, and Heart Rate on the Systolic Thresholds for Detection of Pulmonary Hypertension. Issue 11 (2nd June 2020) - Amsallem, Myriam; Tedford, Ryan J.; Denault, Andre; Sweatt, Andrew J.; Guihaire, Julien; Hedman, Kristofer; Peighambari, Shadi; Kim, Juyong Brian; Li, Xiao; Miller, Robert J. H.; Mercier, Olaf; Fadel, Elie; et al.
Abstract : Background: The strong linear relation between mean (MPAP) and systolic (SPAP) pulmonary arterial pressure (eg, SPAP=1.62×MPAP) has been mainly reported in precapillary pulmonary hypertension. This study sought to quantify the influence of pulmonary arterial wedge pressure (PAWP), heart rate, and age on the MPAP‐SPAP relation. Methods and Results: An allometric equation relating invasive MPAP and SPAP was developed in 1135 patients with pulmonary arterial hypertension, advanced lung disease, chronic thromboembolic pulmonary hypertension, or left heart failure. The equation was validated in 60 885 patients from the United Network for Organ Sharing (UNOS) database referred for heart and/or lung transplant. The MPAP/SPAP longitudinal stability was assessed in pulmonary arterial hypertension with repeated right heart catheterization. The equation obtained was SPAP=1.39×MPAP×PAWP −0.07 ×(60/heart rate) 0.12 ×age 0.08 ( P <0.001). It was validated in the UNOS cohort ( R 2 =0.93, P <0.001), regardless of the type of organ(s) patients were listed for (mean bias [−1.96 SD; 1.96 SD] was 0.94 [−8.00; 9.88] for heart, 1.34 [−7.81; 10.49] for lung and 0.25 [−16.74; 17.24] mm Hg for heart‐lung recipients). Thresholds of SPAP for MPAP=25 and 20 mm Hg were lower in patients with higher PAWP (37.2 and 29.8 mm Hg) than in those with pulmonary arterial hypertension (40.1 and 32.0 mm Hg). In 186 patients with pulmonary arterial hypertension, the predicted MPAP/SPAP was stable over time (0.63±0.03 at baseline and follow‐up catheterization, P =0.43). Conclusions: This study quantifies the impact of PAWP, and to a lesser extent heart rate and age, on the MPAP‐SPAP relation, supporting lower SPAP thresholds for pulmonary hypertension diagnosis in patients with higher PAWP for echocardiography‐based epidemiological studies.